Who's on first? (Abbott and Costello, ,, 2013)
Abbott and Costello's classic comedy routine, reissued for children, features a bear and a rabbit trying to determine the baseball player covering each base.

Chrysanthemum (Mouse Books, ,, 1998)
Chrysanthemum loves her name, until she starts going to school and the other children make fun of it. She was a perfect baby, and she had a perfect name. Chrysanthemum. When she was old enough to appreciate it, Chrysanthemum loved her name. And then she started school. "I'm named after my grandmother," said Victoria. "You're named after a flower." Chrysanthemum wilted. Life at school didn't improve. In fact, it got worse. Then the students were introduced to their music teacher, Mrs. Twinkle. Mrs. Delphinium Twinkle. And suddenly, Chrysanthemum blossomed.

Penny and her doll (Mouse Books, ,, 2013)
Penny instantly loves the doll her grandmother sends her, but finding the perfect name for her is a challenge.

Stella Batts: needs a new name (Stella Batts, 1,, 2012)
When a classmate makes fun of her name, eight-year-old Stella picks a new one for herself, but discovers that the name she abandoned suits her just fine.

The Fran that time forgot (Franny K. Stein mad scientist, 4,, 2005)
When her embarrassing middle name is revealed at school, mad scientist Franny K. Stein experiments with time in order to return to the past and give herself a more dignified name.

Use your words, Sophie (Viking, an imprint of Penguin Group (USA), 2015)
"When Sophie's new sister won't stop crying, only two-year-old Sophie can communicate with her, even if she isn't using her words as her parents want her to"--

Alma and how she got her name (Dreamscape Media, Candlewick Press, 2019)
How did Alma Sofia Esperanza José Pura Candela end up with such a long name? As Daddy tells the story of her many names, Alma can almost feel herself grow into them.

I don't know what to call my cat (Houghton Mifflin Harcourt, HarperCollins, 2017)
Before a little girl has a chance to name the cat that arrives unexpectedly at her house, he disappears again only to be replaced by another "pet," Steve the gorilla.

The boy who tried to shrink his name (Abrams, Abrams Books for Young Readers, 2023)
When Zimdalamashkermishkada starts a new school, he decides to shrink his name to the shorter, simpler Zim, but when his new friend Elly sees him for who he truly is, Zimdalamashkermishkada finds the confidence to step proudly into his long name.

Rump: the true story of Rumpelstiltskin (Alfred A. Knopf, 2013)
Relates the tale of Rumpelstiltskin's childhood and youth, explaining why his name is so important, how he is able to spin straw into gold, and why a first-born child is his reward for helping the miller's daughter-turned-queen.

That's not my name! (Viking Children's Books, 2022)
Mirha questions her name after her classmates continually pronounce it wrong on the first day of school so her mother helps her to learn the significance of her name and to be proud of it.

My name (Farrar Straus Giroux, 2023)
When his name is mispronounced, leading to laughter in the classroom, an Indian American boy is reminded by his parents how special he is and how his unique name reflects that.

What's in a name? (I can read book, ,, 2023)
"Gigi wants to go by something besides her baby name--but her full name, Geraldine, is too long to write and Hanako, her middle name, doesn't feel quite right. Will Gigi find the perfect name?"--

Fifteen animals! (Boynton on board, ,, 2023)
A boy describes his fifteen pets, almost all of which are named Bob.